Crystal Structure of Mycobacterium tuberculosis Elongation Factor G1 - Gao, Xiaopan; Yu, Xia; Zhu, Kaixiang; Qin, Bo; Wang, Wei; Han, Pu; Aleksandra Wojdyla, Justyna; Wang, Meitian; Cui, Sheng (Frontiers in Molecular Biosciences, 2021)
Mycobacterium tuberculosis (Mtb) caused an estimated 10 million cases of tuberculosis and 1.2 million deaths in 2019 globally. The increasing emergence of multidrug-resistant and extensively drug-resistant Mtb is becoming a public health threat worldwide and makes the identification of anti-Mtb drug targets urgent. Elongation factor G (EF-G) is involved in tRNA translocation on ribosomes during protein translation. Therefore, EF-G is a major focus of structural analysis and a valuable drug target of antibiotics. However, the crystal structure of Mtb EF-G1 is not yet available, and this has limited the design of inhibitors. Here, we report the crystal structure of Mtb EF-G1 in complex with GDP. The unique crystal form of the Mtb EF-G1-GDP complex provides an excellent platform for fragment-based screening using a crystallographic approach. Our findings provide a structure-based explanation for GDP recognition, and facilitate the identification of EF-G1 inhibitors with potential interest in the context of drug discovery.